Characterization of Exosporium Layer Variability of Clostridioides difficile Spores in the Epidemically Relevant Strain R20291 - Pizarro-Guajardo, Marjorie; Calderón-Romero, Paulina; Romero-Rodríguez, Alba; Paredes-Sabja, Daniel (Frontiers in Microbiology, 2020)
Clostridioides difficile is a Gram-positive anaerobic intestinal pathogenic bacterium and the causative agent of antibiotic-associated diarrhea and spores are the transmission vehicle of the disease. In C. difficile spores, the outermost exosporium layer is the first barrier of interaction with the host and should carry spore ligands involved in spore-host interactions. C. difficile forms two types of spores (i.e., thin and thick exosporium layers). In this communication, we contribute to understand several biological aspects of these two exosporium morphotypes. By transmission electron microscopy, we demonstrate that both exosporium morphotypes appear simultaneously during sporulation and that the laminations of the spore coat are formed under anaerobic conditions. Nicodednz density-gradient allows enrichment of spores with a thick-exosporium layer morphotype and presence of polar appendage. Using translational fluorescent fusions with exosporium proteins BclA3, CdeA, CdeC and CdeM as well as with several spore coat proteins, we observed that expression intensity and distribution of SNAP-translational fusions in R20291 strain is highly heterogeneous. Electron micrographs demonstrate that multicopy expression of CdeC, but not CdeM, SNAP translational fusion, increases the abundance of the thick exosporium morphotype. Collectively, these results raise further questions on how these distinctive exosporium morphotypes are made during spore formation.